2021
DOI: 10.1126/sciadv.abk0233
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate drives bacterial heterochromatin formation

Abstract: Polyphosphate specifically cooperates with Hfq to silence prophages and mobile genetic elements in the bacterial chromosome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 62 publications
5
35
0
Order By: Relevance
“…On the other hand, the ones that have been known for decades, seem to have an incredibly versatile repertoire of regulatory activities across bacterial species which can expand beyond their interactions with RNA, as shown for Hfq. This pleiotropic regulator has been very recently found to be fundamental for the silencing of prophages and mobile genetic elements by binding to these DNA regions and driving the formation of phase-separated condensates and of heterochromatin-like domains [ 145 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ones that have been known for decades, seem to have an incredibly versatile repertoire of regulatory activities across bacterial species which can expand beyond their interactions with RNA, as shown for Hfq. This pleiotropic regulator has been very recently found to be fundamental for the silencing of prophages and mobile genetic elements by binding to these DNA regions and driving the formation of phase-separated condensates and of heterochromatin-like domains [ 145 ].…”
Section: Discussionmentioning
confidence: 99%
“…One class of large subcellular bodies of particular interest in this context are Hfq-based assemblies. Hfq has been suggested to form several types of biomolecular condensates which may have distinct functions in E. coli : two types of RNA-based assemblies, Hfq-foci and H-bodies, both involved in RNA processing during nitrogen starvation, and DNA-based assemblies, specifically the formation of heterochromatin ( 12 , 36 , 37 ). In the context of heterochromatin, Hfq has been shown in vitro to form phase separated assemblies with DNA and polyP ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in C. crescentus , it has been shown that disrupting cell cycle progression can in turn alter granule organization ( 6 ). Recently polyP has been suggested to interact with the nucleoid associated protein (NAP) Hfq in Escherichia coli and promote Hfq-mediated transcriptional silencing ( 12 ). Together, these observations indicate that the polyP polymer and polyP granules are structurally and functionally linked to the chromosome in diverse bacterial species.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic polyphosphate (polyP) is a linear polymer of 3-1000 phosphate units that is produced by organisms of all domains of life [1][2][3]. Bacterial polyP is well known to be important for stress response through diverse mechanisms, including roles in metal chelation [4,5], resistance to oxidants [6], unfolded and damaged protein stabilization [7], and DNA metabolism [8][9][10], and plays a major role in virulence in many pathogens [6,11,12]. Recent work has also begun to decipher the molecular mechanisms by which bacterial polyP directly disrupts phagocytic cell functions important in the host immune response to bacterial infections [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%